Religious Tourism in Greece and regional development: The case of Samos Island - Chrysanthi Balomenou; Panoraia Poulaki; Dimitrios Lagos (European Regional Science Association (ERSA), 2015)
Religious tourism and tourism in general helps in the development and intensification of social and cultural relations. The issue of religious tourism comes under the general and sustainable development of alternative tourism, special interest and respect for holy places. Religious tourism is an emerging form of tourism which aims to quality and sustainable development. It places special emphasis on preservation, revival and development of religious and historical monuments for the creation of tourist flows. The pilgrimage was and it will continue to be an important motivation movement of people and this often associated with religious and historical value of monasteries or churches, religious celebrations and various historical events. Religious tourism can be further strengthened internationally if the areas of the tourist destination dispose various tourist resources apart from religious monuments. The religious and historical monuments are attractive tourist destinations internationally and in Greece. Samos is one of the richest islands in Greece as far as the religious and historical monuments are concerned and for this reason is one of the most suitable for the development of religious tourism. It disposes important religious attractions that are an integral part of the national heritage and attract tourists who may be part of propellant development of religious tourism. Samos for a long time has been distinguished for piety of its inhabitants and for its intense ecclesial life. This is testified by the many parish churches, its chapels, its private temples, and many of the monastic churches. Samos is distinguished for its very important and interesting cultural heritage with many Byzantine monuments, many remarkable archaeological finds, rich exhibits at museums, castles, monasteries, churches, et al. Samos has important religious sites, monasteries and churches, which are part of the national heritage and attract tourists. The main aim of this paper is to explore the prospects for the development of religious tourism of the island of Samos and to gauge its contribution to the regional development in Greece. Samos has the ability to develop religious tourism because the island has important religious and historical sites. In order to investigate the possibilities and prospects of development of religious tourism in Samos it was conducted a survey concerning the status quo and recording problems that hinder its development. For this purpose quantitative research conducted by using a closed questionnaire and the method of stratified sampling. This investigation showed that Samos as a religious destination has not been developed enough, but it has many prospects of growth. It is required to provide a framework of tourism policy at local level, which will include a number of selected actions for the planning and management of religious tourism.
Keywords: L83; O18; 330; Religious Tourism; Samos; Religious Monuments; Monasteries; Churches; Sanctuarie